Invariant natural killer T cells in adipose tissue: novel regulators of immune-mediated metabolic disease - Rakhshandehroo, M; Kalkhoven, E; Boes, M (Cellular and molecular life sciences : CMLS, 2013)
Adipose tissue (AT) represents a microenvironment where intersection takes place between immune processes and metabolic pathways. A variety of immune cells have been characterized in AT over the past decades, with the most recent addition of invariant natural killer T (iNKT) cells. As members of the T cell family, iNKT cells represent a subset that exhibits both innate and adaptive characteristics and directs ensuing immune responses. In disease conditions, iNKT cells have established roles that include disorders in the autoimmune spectrum in malignancies and infectious diseases. Recent work supports a role for iNKT cells in the maintenance of AT homeostasis through both immune and metabolic pathways. The deficiency of iNKT cells can result in AT metabolic disruptions and insulin resistance. In this review, we summarize recent work on iNKT cells in immune regulation, with an emphasis on AT-resident iNKT cells, and identify the potential mechanisms by which adipocytes can mediate iNKT cell activity.